Balance Performance Is Task Specific in Older Adults. (5th September 2017) - Dunsky, Ayelet; Zeev, Aviva; Netz, Yael
Abstract : Balance ability among the elderly is a key component in the activities of daily living and is divided into two types: static and dynamic. For clinicians who wish to assess the risk of falling among their elderly patients, it is unclear if more than one type of balance test can be used to measure their balance impairment. In this study, we examined the association between static balance measures and two dynamic balance field tests. One hundred and twelve community-dwelling older adults (mean age 74.6) participated in the study. They underwent the Tetrax static postural assessment and then performed the Timed Up and Go (TUG) and the Functional Reach (FR) Test as dynamic balance tests. In general, low-moderate correlations were found between the two types of balance tests. For women, age and static balance parameters explained 28.1–40.4% of the variance of TUG scores and 14.6–24% of the variance of FR scores. For men, age and static balance parameters explained 9.5–31.2% of the variance of TUG scores and 23.9–41.7% of the variance of FR scores. Based on our findings, it is suggested that a combination of both static and dynamic tests be used for assessing postural balance ability.